The Influence of Work Hour Flexibility and Work Environment on Employee Productivity at the Youth and Sports Office, Culture and Tourism of Labuhanbatu Regency - Chairunisya, Chairunisya; Nasution, Novrihan Leily; Hanum, Fauziah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of work hour flexibility and work environment on employee productivity at the Department of Youth and Sports, Culture and Tourism of Labuhanbatu Regency. The research employed a quantitative approach using a survey method through questionnaires distributed to 81 respondents. Data were analyzed using multiple linear regression with the assistance of SPSS version 24. The results show that both work hour flexibility and work environment have a positive and significant effect on employee productivity, either partially or simultaneously. The coefficients of determination (R2) value of 0,202 indicates that 20,2% of the variation in employee productivity can be explained by these two variables, while the remaining 79,8% is influenced by other factors outside the model. These findings suggest that implementing flexible working hours and fostering a supportive work environment significantly contribute to enhancing efficiency, motivation, and productivity among employees in public sector institutions.